KAJIAN KINERJA SISTEM IRIGASI DI DAERAH IRIGASI PANDRAH KABUPATEN BIREUEN - Winardi Winardi; Azmeri Azmeri; Masimin Masimin (Prodi Magister Teknik Sipil Unsyiah, 2020)
The Pandrah Irrigation Area is a technical irrigation network whose water source comes from the Krueng Pandrah river. Pandrah Weir was built in 1987 located in Samagadeng Village, Pandrah District, Bireuen Regency. It has an area of 1,203 hectares of irrigated rice fields. In its development, the damage that occurs in the Pandrah irrigation area also cannot be ignored. It is necessary to review it by assessing the performance of the irrigation system. The purpose of this study was to determine the performance index of the Pandrah irrigation system using the MASSCOTE (Mapping System and Service for Canal Operation Technique) method approach. The assessment of the performance index of the Pandrah irrigation system using the MASSCOTE method approach is carried out by evaluating the Rapid Appraisal Procedure (RAP) on four main indicators, namely service indicators, indicators for Farmers Using Water (P3A), indicators for the operator's Human Resources (HR). In the evaluation of the RAP, it is the value of observations of the respondents of OP officers and P3A farmers who are presented in a questionnaire to cross-assess each respondent in irrigation management. The results of the research on the performance appraisal of the Pandrah irrigation system based on the MASSCOTE method with RAP evaluation showed that the performance index of the absolute value (Level of Service) was 3.05. Hence, the performance index of the Pandrah irrigation system in the existing conditions was in the Good classification. This index and classification value shows the value of irrigation operations in fulfilling services from irrigation management carried out by operators / OP officers and felt by irrigation service beneficiaries, namely P3A farmers.